2018
DOI: 10.1063/1.5046529
|View full text |Cite
|
Sign up to set email alerts
|

Green’s function coupled cluster formulations utilizing extended inner excitations

Abstract: In this paper we analyze new approximations of the Green's function coupled cluster (GFCC) method where locations of poles are improved by extending the excitation level of inner auxiliary operators. These new GFCC approximations can be categorized as GFCC-i(n, m) method, where the excitation level of the inner auxiliary operators (m) used to describe the ionization potentials and electron affinities effects in the N −1 and N +1 particle spaces is higher than the excitation level (n) used to correlate the grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 107 publications
2
42
0
Order By: Relevance
“…Note that, in Fig. 4c (and its inset), by extrapolating the six-frequency model from the regime of [-304.77, -293.89] eV to [-326.57, -293.89] eV, three significant satellites, which were not reported in the previous GFCC-i (2,3) calculations, [66] are identified at -320.85, -315.41, and -308.88 eV, respectively (a weaker shoulder peak can also be seen at ∼-316.77 eV). The configuration analysis shows that these satellites are mainly attributed to the 1π −1 2σ −1 1π * two-electron process (classified as the so-called direct shake-up states), and are consistent with the configuration analysis of the satellites obtained from GFCCSD/GFCCSD-MOR To further test the efficiency of the proposed GFCC-MOR method, we examine its application to some larger systems.…”
Section: )mentioning
confidence: 65%
See 2 more Smart Citations
“…Note that, in Fig. 4c (and its inset), by extrapolating the six-frequency model from the regime of [-304.77, -293.89] eV to [-326.57, -293.89] eV, three significant satellites, which were not reported in the previous GFCC-i (2,3) calculations, [66] are identified at -320.85, -315.41, and -308.88 eV, respectively (a weaker shoulder peak can also be seen at ∼-316.77 eV). The configuration analysis shows that these satellites are mainly attributed to the 1π −1 2σ −1 1π * two-electron process (classified as the so-called direct shake-up states), and are consistent with the configuration analysis of the satellites obtained from GFCCSD/GFCCSD-MOR To further test the efficiency of the proposed GFCC-MOR method, we examine its application to some larger systems.…”
Section: )mentioning
confidence: 65%
“…Note that, due to stronger many-body effect in the inner valence regime, it usually requires much more effort for the linear solver to converge the GFCC linear system for the X p 's in that domain than it does for the X p 's in the outer valence regime. [65,66] Therefore, in comparison to the model in Fig. 1b, the model in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, we also assumed that Λ int = T † int (the efficiency of this approximation was discussed in Refs. [55]). (1)int , Q N −1…”
Section: Approximations and Implementation Detailsmentioning
confidence: 99%
“…We demonstrated that the GFCCi(2,3) approximation can significantly improve the location of satellite peaks compared to the GFCCSD formalism. [55] For this reason we decided to combine the GFCC-i(2,3) approach with the DUCC effective Hamiltonians (DUCC-GFCC-i(2,3) approach).…”
Section: Approximations and Implementation Detailsmentioning
confidence: 99%